Impact of the COVID-19 pandemic on pediatric dentistry procedures carried out in the Unified Health System in the state of Tocantins: Difference between the years 2018 and 2022 (Research, Society and Development, 2024)
Introduction: Due to the pandemic, there were changes in dental care in order to contain the spread of the disease. Dental care was restricted to urgent and emergencies for a period of time. And as a result, children's oral health may have been negatively impacted. Objective: The present study aimed to investigate the difference in the number of procedures carried out by the Unified Health System before and during the Covid-19 pandemic, from 2018 to 2022. Methodology: A descriptive study with an ecological design was carried out, based on the Ambulatory Information System (SIA/SUS) of the SUS Information Technology Department (Datasus). The percentage difference in procedures between the periods analyzed was calculated, as well as the relative and absolute frequencies. Results and discussion: 53,148 pediatric dental procedures were performed, 37,257 in the period before the pandemic and 15,891 during the pandemic, resulting in a reduction of 57.3%. Conclusion: There was a decrease in the number of dental procedures on primary teeth in the state of Tocantins, between the periods analyzed. This highlights the need for planning and the importance of reflecting on this new reality.